2007
DOI: 10.1038/sj.bjp.0707406
|View full text |Cite
|
Sign up to set email alerts
|

Activation of BKCa channels via cyclic AMP‐ and cyclic GMP‐dependent protein kinases by eugenosedin‐A in rat basilar artery myocytes

Abstract: Background and purpose: The study investigated whether eugenosedin-A, a 5-hydroxytryptamine and a/b adrenoceptor antagonist, enhanced delayed-rectifier potassium (K DR )-or large-conductance Ca 2 þ -activated potassium (BK Ca )-channel activity in basilar artery myocytes through cyclic AMP/GMP-dependent and -independent protein kinases. Experimental approach: Cerebral smooth muscle cells (SMCs) were enzymatically dissociated from rat basilar arteries. Conventional whole cell, perforated and inside-out patch-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Several previous reports have suggested that the activation of the sGC-mediated increase in cGMP plays an important role in vasodilation by activation of BK Ca channels (42,43). Therefore, application of YC-1 could increase the K + efflux by activating BK Ca channels, although this conflicts with the observation that YC-1 induces Kv-channel inhibition.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Several previous reports have suggested that the activation of the sGC-mediated increase in cGMP plays an important role in vasodilation by activation of BK Ca channels (42,43). Therefore, application of YC-1 could increase the K + efflux by activating BK Ca channels, although this conflicts with the observation that YC-1 induces Kv-channel inhibition.…”
Section: Discussioncontrasting
confidence: 53%
“…However, in our experimental conditions, the activation of BK Ca channels were minimized by the inclusion of 10 mM BAPTA, a Ca 2+ chelator, in the pipette solution and the pretreatment with iberiotoxin (100 nM), a specific BK Ca -channel inhibitor, in the bath solution. Also, it has been reported that agonist-mediated activation of BK Ca channels through cAMP and cGMP-dependent protein kinases could be inhibited with treatment of 100 nM iberiotoxin (43). Therefore, we are confident that under our experimental conditions, there is a minimal contribution of BK Ca to the Kv currents.…”
Section: Discussionmentioning
confidence: 48%
“…3), respectively, based on the use of selective inhibitors of these kinases and/or direct application of biochemically purified kinase to the cytoplasmic face of excised, inside-out membrane patches containing BK Ca [60,[120][121][122][123][124][125][126]. For example, BK Ca activation by cAMP/PKA was observed in murine renal artery [127] and rat pulmonary artery [128].…”
Section: Hyperpolarization Of the Smooth Muscle Cell Membrane Potentimentioning
confidence: 99%
“…In the present study we did not assess the potential effect of KT5823 alone on SERCA2b expression; instead, we determined the inhibitory effect of KT5823 against the E2‐mediated increase in SERCA2b expression. However, previous reports have suggested that KT5823 alone has similar effects as the control when evaluating the cGMP/PKG pathway in arterial endothelial and smooth muscle cells …”
Section: Discussionmentioning
confidence: 95%